Orientalist Writings on the History of Algeria: The Writings of the French Orientalist François de Villaret on the History of Djelfa as a Model. (Revue El-Wahat pour les Recherches et les Etudes, 2025)
François de Villaret was born in Angers, western France, in 1913. He joined the White Fathers Institute and was appointed bishop of Carthage, Tunisia. In 1945, he moved to Algeria and settled in Djelfa until 1948, later moving between El Bayadh and Touggourt until the end of the Algerian War of Independence.De Villaret mastered Arabic, and his primary mission was spreading Christian teachings. After his missionary project failed, he focused on the region's history, relying on French archival documents and writings of French military leaders and translators, especially from the 19th century like Marey-Monge and Arnaud.His notable work on Djelfa's history, “Siècles de Steppe” (The Steppes Through the Ages), consists of two volumes covering prehistory to French colonization and resistance movements in the 19th century.Keywords: Djelfa, De Villaret, Steppes, Oulad Nail, Resistance.